Value Disintegration and Its Relation to the Spread of Negative Behaviors Among Libyan Youth - Al-Rayani, Ali Mohammed Al-Rayani ((Faculty of Arts Journal) مجلة كلية الآداب - جامعة مصراتة, 2016)
The study of values holds a significant position in sociology due to their close relationship with behavioral motivations, goals, and social judgments. This study aims to explore the role of values in reinforcing certain aspects of social deviance, particularly among youth, in the context of the ongoing social transformations within Libyan society. Deviant behavior is seen as a violation of prevailing social norms and values, and understanding it requires systematic and intellectual inquiry. The current study attempts to shed light on the hidden value systems that may contribute to deviant behaviors, emphasizing the importance of structured scientific research in understanding the dynamic relationship between values and deviance.